Economic growth and development in Barbados during the twentieth century - Downes, Andrew S. (2001)
Examines the growth and development of the Barbadian economy since 1900. Identifies some key factors accounting for economic growth in Barbados, which can explain why it has performed fairly well when compared with different countries in the Caribbean region.